Database Forensics in Software as A Service Service using Stored Procedure - Rusydi Umar; Imam Riadi; Purwanto Purwanto (Institute of Computer Science (IOCS), 2022)
Recently, the use of web-based applications has increased significantly, especially online services, most of which are used for digital transaction activities that use the internet. However, the increasing use of online services often ignores the privacy and security aspects of an application, web developers making it an attractive target for security concerns. In this article, the proposed countermeasures include two mechanisms, namely: the use of stored procedure parameters, and the use of stored procedure encryption in SQL server. The goal is to prevent the dangers of internet crime attacks using structured query language injection attacks (SQLIA). In addition, an analytical evaluation of prevention and protection should also be carried out. The solution offered is prevention and protection using stored procedures because it can prevent SQLI attacks effectively and efficiently.